Giuseppe Dessí. Storia e genesi dell'opera con una bibliografia completa degli scritti di e sull'autore - Turi, Nicola (Moderna/Comparata, 2014)
As scattered pieces of a composite artistic path to be reassembled, the personal notes, writing tests, private letters and reviews kept by Giuseppe Dessí over the years allow Nicola Turi, who had already been following the author's footsteps for some time, to reconstruct the sources of inspiration, the composition and revision processes, as well as the main stages of the critical reception of a work crossing the best part of the 20th century in Italy with an elegant gait which constantly brings it in on the same level as the great European models: a philosophical background which is always up to date, and the very fine sensitivity of someone who knows how to grasp the imperceptible movements of the human soul and the great changes of history at the same time. This volume is the result of a long archival work and, also by virtue of the bibliography (by and on the author) placed in the appendix, it aims at functioning as a journey through Dessí's texts and, at the same time, at offering the readers the necessary hermeneutical support to understand his works.